A Looping Material of (CoO+1.0% PtO2)/CoAl2O4 for Dimethyl Ether Chemical-looping Combustion in a Cellular Reactor. (July 2017) - Hong, Hui; Zhang, Hao; Han, Tao; He, Fengjuan; Jin, Hongguang
Abstract: Chemical-looping combustion (CLC) is considered as one of innovative technologies for CO2 capture. In this paper, an oxygen carrier of (CoO+1.0% PtO2 )/CoAl2 O4 is synthesized for the mid-temperature chemical-looping combustion of di-methyl ether (DME). Experiments are implemented to investigate the reactivity, the carbon deposition behavior and the redox stability. Experimental results indicate that the looping material shows a good reactivity at reduction temperature of 673 K. Furthermore, we propose a cellular combustor reactor which has a potential of eliminating the gas-solid separation and avoiding the abrasion of solid looping material. Our study has provided the possibility for the integration of the mid-temperature solar thermal energy with the chemical-looping combustion of DME, and offering a new approach of developing the combustor reactor of the chemical-looping combustion.